Situational information and the design of representative learning tasks: What impact does a scoreboard have on expert taekwondo fighters' behaviour and affective-cognitive responses?. (July 2022) - Maloney, Michael A.; Renshaw, Ian; Greenwood, Daniel; Farrow, Damian
Abstract: Designing representative learning tasks is one means to enhance sports practice. Recent work has highlighted how the presence of situational information could help the design of these tasks by shaping intentions and enhancing the affective demands of practice, however this has yet to be empirically tested. This study tested this hypothesis by manipulating the presence of a scoreboard featuring time and score situational information as expert taekwondo athletes fought in practice. Nine taekwondo fighters fought with and without situational information in a counterbalanced order. Behaviour was assessed by tracking fighters' location coordinates to assess fighter-fighter dyad coordination and through notational analysis of attacking actions. Affect and cognition were assessed with mixed-methods that included perceptual scales measuring anxiety, arousal, mental effort, score perception, and post-fight video-facilitated confrontational interviews to explore how conditions differed. The results revealed that the presence of the situational information had significant effects on taekwondo players. When present, fighters reported greater cognitive anxiety (d = 0.39, p < 0.05), somatic anxiety (d = 1.11, p < 0.05) and emotion intensity (d = 0.33, p < 0.05). The enhanced affective demands were associated with behaviour changes that included fighters preferring to spend time at closer distances (d = 0.25, p < 0.05), and more predictable technique selection (d = 1.04, p < 0.05). Qualitative data supported these findings. Players also reported their intentions were coupled to the context of scoreboard. This study reveals that situational information changes the affective and behavioural demands of practice to be more like competition. Further, situational sampling affords performers the opportunity to practice attuning to the relevant affordances for a specific context. Highlights: Situational information shapes the affect, behaviour, and cognition of taekwondo athletes When fighting with a scoreboard, athletes had higher anxiety and arousal Intentions were constrained by time and score, with actions afforded different levels of functionality pending the situation Situational information led to a more engaging practice task The design of representative learning tasks should consider the role of situational information